DEMOCRATIZATION PROCESS AND OPPOSITION PARTY IN NIGERIA: AN INSIGHT - IDREES MAHMUD GANA; OGAJI TIJANI ADAMU (International Studies Journal)
As a potent opposition to the ruling party, political parties perform one of the most significant functions in a democracy. Though political opposition is essential to the functioning of self-governing institutions and societies, the role of opposition parties in developing democracies like Nigeria has gotten little attention. Based on this, the research aims to investigate Nigeria's opposition party and democratic process. The Theory of Consensus Democracy and Prebendalism Theory serve as the theoretical foundation for this study. The overall weakness of Nigeria's political opposition was revealed through qualitative examination of material that was mostly collected from secondary sources. The study asserted that among other things, fragmentation, violence, desertion, manipulation of election rules, and money politics are to blame for political parties' inability to function as effective platforms for opposition to the ruling party. The study suggests, among other things, that Nigerians and the media oppose increased political chances. Additionally, the supporters of the competing parties must immediately mobilize the voter. This circumstance is an out different from how they have always been marketed as being reachable in developed countries.